Disponibilidade de fósforo em solo tratado com resíduos urbanos e industriais sob sistema de plantio direto cultivado com soja - Santos, Susiane de Moura Cardoso dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Industrial and municipal wastes applied to agricultural crops under no-tillage (NT) can promote benefits in physical, chemical and biological soil properties. The reuse of these materials reduces the supply of synthetic fertilizers, providing greater economic and environmental sustainability. Apart from acting as attenuators of soil acidity, some of these residues are excellent sources of plant nutrients such as phosphorus (P). Understanding the dynamics of P arising from waste and applied in tropical soils is important to assist in fertilization management of agricultural species. In this context, the objective of this study was to analyze the chemical changes in the soil, mainly through the fractionation of P, and to assess the nutritional status and grain yield of soybean plants grown under no-tillage (NT) in an Oxisol that received application of municipal and industrial waste. The experimental design was randomized blocks, 4x3+2 factorial scheme with three replications. Treatments were four residues LC - centrifuged sewage sludge with addition of quicklime (CaO); LB - sewage sludge from the digester with the addition of polyelectrolytes; and - steel slag; and LCAL - lime slurry applied at dosages of 0, 2, 4 and 8 mg ha-1. In soil sample collected in the 0-5, 5-10, 10-20 and 20-40 cm depth was held fractionation of soil P (RTA Pi, Pi Po and NaOH 0.1 mol L-1, HCl Pi, Pi Po and NaOH 0.5 mol L-1, residual P) and evaluated some characteristics of soil pH, organic matter, V%, P, Ca and Mg. In the plant, we assessed the nutritional status, through the determination of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn in the leaves and grain yield. It was found that the application of the waste, along with the annual planting fertilization, contributed to a significant increase and preferred organic forms of phosphorus in the soil, and the LB and ...

Resíduos industriais e urbanos aplicados em cultivos agrícolas sob sistema de plantio direto (SPD) podem promover benefícios nos atributos físicos, químicos e biológicos do solo. A reutilização desses materiais reduz o aporte de fertilizantes, proporcionando maior sustentabilidade ambiental e econômica. Além de atuarem como atenuadores da acidez do solo, alguns desses resíduos são excelentes fontes de nutrientes de planta, como o fósforo (P). O entendimento da dinâmica do P advindo de resíduos e aplicados em solos tropicais é importante para auxiliar no manejo da adubação de espécies agrícolas. Neste contexto, objetivou-se com este estudo, analisar as alterações químicas no solo, principalmente, por meio do fracionamento do P, bem como avaliar o estado nutricional e a produtividade de grãos da cultura da soja cultivada sob sistema de plantio direto (SPD) em um Latossolo Vermelho distrófico que recebeu aplicação de resíduos urbanos e industriais. O delineamento experimental adotado foi em blocos ao acaso, em esquema fatorial 4x3+2, com três repetições. Os tratamentos foram constituídos por quatro resíduos: LC - lodo de esgoto centrifugado com adição de cal virgem (CaO); LB - lodo de esgoto proveniente de biodigestor com adição de polieletrólitos; E - escória de aciaria; e Lcal - lama cal, aplicados nas doses 0, 2, 4 e 8 Mg ha-1. Em amostra de terra coletadas nas camadas de 0-5, 5-10, 10-20 e 20-40 cm de profundidade,realizou-se o fracionamento de P no solo (Pi RTA, Pi e Po NaOH 0,1 mol L-1, Pi HCl, Pi e Po NaOH 0,5 mol L-1, P residual) e ...
Availability of phosphorus in soil treated municipal wastes and industrial system under direct planting with soybean grown
Keywords: Soja - Cultivo; Lodo de esgoto; Plantio direto; Resíduos; Soja